Could heart rate be regarded as cardiovascular disease risk factor? - V. I. Makolkin; F. N. Zyabrev (Кардиоваскулярная терапия и профилактика)
The article is devoted to the role of increased heart rate (HR) as cardiovascular disease predictor. Many epidemiological studies demonstrate the link between this parameter and total and cardiovascular mortality. The authors describe rhythm-decelerating therapy with a new medication – ivabradine, specifically affecting sinus node function. Pilot studies confirm its antianginal efficacy, pointing to its potential in stable coronary heart disease management.